A systematic review of prenatally diagnosed vein of Galen malformations: prenatal predictive markers and management from fetal life to childhood - Lavinia Di Meglio; Giordana Sica; Paolo Toscano; Giuliana Orlandi; Luigi Manzo; Laura Letizia Mazzarelli; Laura Letizia Mazzarelli; Carmine Sica; Aniello Di Meglio (Frontiers Media S.A., 2024)
IntroductionVein of Galen malformations (VGMs) account for less than 1% of all intracranial vascular malformations. However, in fetal and pediatric populations, they represent the most common vascular malformation of the brain. For the effective management of this condition, an optimal knowledge of its prenatal and postnatal clinical features is mandatory.MethodsArticles published between 1 January 2003 and 31 January 2024, reported in PubMed and EMBASE, were evaluated for a systematic review analyzing the prenatal and postnatal features and management of fetal VGMs.ResultsThirty-one papers reporting information on 51 prenatally diagnosed VGMs were included. The most common prenatal features were fetal hydrocephalus (39%) and cardiomegaly (56%). Postnatal data for 43 VGM cases are described. The overall mortality was 58.14%. In total, 77.78% of the survivors had normal development.ConclusionsClose follow-up and a multidisciplinary approach are mandatory to manage this condition. Our study aimed to provide a guide for gynecologists, neonatologists, cardiologists, and neuroradiologists.